Understanding technoscientific citizenship in a low-carbon Scotland - Gibbs, Beverley (2015)
Public engagement with science and technology is a vibrant topic of interest in the United Kingdom, offering promises of democratic and informed governance and a supportive and trusting public. In this context, the idea of ‘scientific citizenship’ is gaining ground, though it remains nebulous in both theory and practice with contested, overlapping and unarticulated representations of its origins, meaning and purpose. The aim of this thesis is to unpack the notion of scientific citizenship, in particular, questions relating to: who counts as a scientific citizen, what rights do they have as citizens and how are scientific citizens meant to engage with science.